Effects of the anabolic steroid nandrolone on the soleum muscle of rats submitted to physical training through swimming: Histological, histochemical and morphometrical study - Camargo Filho, José Carlos Silva [UNESP]; Vanderlei, Luiz Carlos Marques [UNESP]; Camargo, Regina Celi Trindade [UNESP]; Francischeti, Fabiana Acorse [UNESP]; Belangero, Willian Dias; Dal Pai, Vitalino [UNESP] (My University, 2006)
The objective of this study was to analyze the histological, histochemical and morphometrical alterations of the fibers from the soleum muscle of rats submitted to a swimming program, associated or not to the administration of the anabolic steroid decanoate of nandrolone. 22 male Wistar rats were used, 12 of which received a muscle injection of steroid (5 mg/kg) and 10 received mineral oil (5 mg/kg), twice a week. The animals were submitted to 42 sessions of swimming during nine weeks (from Monday to Friday), with gradual load increase through the swimming time. After sacrifice, the left soleum muscle was removed, immersed in n-hexane and conditioned in liquid nitrogen. Third middle cuts of this muscle were made in microtome cryostat (-20°C), and stained through HE technique and through NADH-TR histochemic method. The animals submitted to physical training and steroid (TA) or mineral oil (TO) presented muscle fibers with bigger diameter when compared to the ones from the control group (NTA and NTO). There was not significant difference between NTA and NTO and between TA and TO groups fiber diameters measures. In the TA and NTA groups, severe process of phagocytes, rounding and hyalinization of muscle fibers was observed. On the other hand, in the TA, TO and NTA groups, loss of the oxidative enzymatic activity was seen. The results suggest that swimming produces muscle hypertrophy similarly, not only in the group that received steroid, but also in the one that received mineral oil. However, the group that received steroid presented clear signs of greater muscle degeneration.
Efeitos do esteróide anabólico nandrolona sobre o músculo sóleo de ratos submetidos a treinamento físico através de natação: Estudo histológico, histoquímico e morfométrico
Keywords: Histology; Hypertrophy; Injury